PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN LABORATORIUM VIRTUAL TERHADAP KEMAMPUAN REPRESENTASI GRAFIK SISWA SMA DI SEKOLAH - Laily Ahila Qurrotul Firdausi; I Ketut Mahardika; Supeno Supeno (Universitas Jember, 2021)
This study aims to determine the effect of the guided inquiry learning model assisted by a virtual laboratory on the graphic representation ability of high school students in schools. The multi-representation used in this study is a graphical representation. This study uses a quasi-experimental method with a post test only design. The sample used in this study was taken by purposive sampling technique. This research was conducted at SMAN Pakusari with the research subjects of class X MIA 4 as the experimental class and class X MIA 1 as the control class. Data collection techniques using tests, tests in this study as data collection containing questions / exercises that are used to measure the ability of graphic representation owned by each individual. Based on the results of the t-test, with the 2 independent sample t-test or Mann-Whitney U test, it can be seen that the output of the Statistic Test for the asymp value. Sig. (2-tailed) that is 0.002 < 0.05 so that there is a significant effect between the ability of graphic representation in the experimental class and the control class. Keywords: Guided Inquiry, Virtual Laboratory, Graphic Representation Ability